2002
DOI: 10.1007/s00240-002-0248-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of antisense oligonucleotides in the treatment of bladder cancer

Abstract: Both intravesical and systemic chemotherapy are limited in their efficacy in the treatment of bladder cancer patients. These limitations are centred around an inability to induce apoptosis in bladder tumour cells. This resistance to apoptosis induction is commonly associated with the overexpression of antiapoptotic proteins such as Bcl-2. Strategies to decrease the cellular expression of such proteins would enhance chemotherapy effectiveness. One such strategy is to use antisense oligonucleotides which are sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…No previous report has addressed the direct effect of MVAC therapy on bcl-2 status in tumor cells. However, bcl-2 overexpression in bladder tumor cells has been characterized as being chemo-resistant, and the role of antisense oligonucleotides of bcl-2 in the treatment of bladder cancer is currently under consideration for use in a new potent therapeutic strategy [24]. Our study demonstrated a significant anti-apoptotic effect of bcl-2 protein in the AGM-1470-treated group, and we found the same tendency in the MVAC-treated group.…”
Section: Discussionsupporting
confidence: 73%
“…No previous report has addressed the direct effect of MVAC therapy on bcl-2 status in tumor cells. However, bcl-2 overexpression in bladder tumor cells has been characterized as being chemo-resistant, and the role of antisense oligonucleotides of bcl-2 in the treatment of bladder cancer is currently under consideration for use in a new potent therapeutic strategy [24]. Our study demonstrated a significant anti-apoptotic effect of bcl-2 protein in the AGM-1470-treated group, and we found the same tendency in the MVAC-treated group.…”
Section: Discussionsupporting
confidence: 73%
“…The accessibility of the bladder mucosa and the low systemic absorption through the bladder wall make intravesical therapy an excellent route of administration of ASO. Although no studies have yet been reported that assess pharmacokinetic and pharmacodynamic activity of ASO after intravesical delivery in humans, preclinical studies would suggest that ASO are taken up by urothelium (47,48). Interestingly, the only approved clinical indication for an ASO is for intravitreal injection of cytomegalovirus-induced retinitis in human immunodeficiency virus, illustrating the potential clinical utility of local instillation for this class of therapeutics (49).…”
Section: Ogx-427 Down-regulation Of Hsp27 In Bladder Cancermentioning
confidence: 99%
“…Despite very high transfection rates of UMUC-3 cells in vitro, we observed limited in vivo penetration of AS-ODNs. Inconsistent Wndings on AS-ODN delivery and uptake have been published, depending on the type of tumors, malignant potential and experimental setting (Duggan et al 2002;Kunze et al 2008;Zhao et al 1998). In a recent report nucleic acid penetration into heterotopic UC was achieved, but predominantly present in the peripheral areas of the tumor (Kunze et al 2008).…”
Section: Figmentioning
confidence: 92%